Killing for land in early California Indian blood at Round Valley : founding the Nome Cult Indian Farm - Baumgardner, Frank H. (Algora Pub., 2006)
"This is a history of the clash between the White settlers and the Native Americans in what is now an affluent county in California. The frontier wars gave land and gold to Whites and reservations to the Native Americans. Eyewitness accounts and extensive research show the conflicting roles played by the Army, State Legislature and the US Congress"--Provided by publisher.